2018
DOI: 10.1155/2018/5192647
|View full text |Cite
|
Sign up to set email alerts
|

Can Diaphragm Dysfunction Be Reliably Evaluated with Pocket-Sized Ultrasound Devices in Intensive Care Unit?

Abstract: Background Diaphragm dysfunction (DD) is frequently seen in critically ill patients, and ultrasound could be a useful tool to detect it and to predict extubation success or failure in mechanically ventilated patients. Besides, it would also be useful in differential diagnosis of dyspnea and respiratory failure. The aim of this study is to evaluate usefulness and accuracy of pocket-sized ultrasound devices (PSDs) in assessment of DD in intensive care unit (ICU) patients in comparison with standard ultrasound de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 28 publications
0
13
0
1
Order By: Relevance
“…Two articles not included in this review showed good overall agreement for detecting B-lines in patients with heart failure, as well as for visualising the diaphragm [37,38]. Some articles concerning hand-held ultrasound in abdominal pathology were not limited to comparing hand-held ultrasound devices with a specific high-end system [29,39,40,41], but were compared with other diagnostic measures, such as physical examination, CT and MRI, as well as US and were not included in this paper.…”
Section: Discussionmentioning
confidence: 99%
“…Two articles not included in this review showed good overall agreement for detecting B-lines in patients with heart failure, as well as for visualising the diaphragm [37,38]. Some articles concerning hand-held ultrasound in abdominal pathology were not limited to comparing hand-held ultrasound devices with a specific high-end system [29,39,40,41], but were compared with other diagnostic measures, such as physical examination, CT and MRI, as well as US and were not included in this paper.…”
Section: Discussionmentioning
confidence: 99%
“…The Vscan has been has used in a previous study to assess its accuracy in the measurement of diaphragm thickness at both tidal and maximal end points of respiration [26]. The authors found that measurements of muscle thickness at both inspiration and expiration gave ICC values of greater than 0.9, at both tidal and maximal volumes.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the use of PSUDs (for lung, heart and inferior vena cava USG) in the evaluation of patients who are admitted to emergency services with acute respiratory problems is feasible, reliable, and beneficial for high yield and speed [12]. Similarly, PSUDs are also found to be as efficient as SUDs in the evaluation of thickening and excursion of the diaphragm in ICU patients, but the quality of the image is low in obese and edematous patients [13]. Also, PSUDs are reliable in demonstrating proximal deep venous thrombosis compared to venous duplex USG [19].…”
Section: Discussionmentioning
confidence: 99%
“…With the development of technology, the USG devices are getting smaller and handheld or pocket-sized USG devices (PSUD) are in use. The number of studies investigating their accuracy and reliability in the evaluation of various organ systems in ICU patients has been increasing day by day [12][13][14]. Their validity has been tested for cardiac, abdominal, and vascular (IVC, lower extremity venous Doppler, jugular cannulation e.g.)…”
Section: Introductionmentioning
confidence: 99%